Transformasi Strategis Pendidikan Berkelanjutan: Implementasi Prinsip Deming dalam Membangun Kolaborasi, Inovasi, dan Orientasi Masa Depan - Madhakomala, R.; Crispinus Lemba, Vinsensius; Megafajari, Dhioatmaja (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2026)
This study aims to formulate a strategic transformation model for sustainable education based on W. Edwards Deming’s principles of quality management. Twenty-first century education faces complex challenges arising from the Fourth Industrial Revolution, digital disruption, and social inequality, demanding a system that goes beyond academic orientation to emphasize sustainability, collaboration, and innovation. Using a Systematic Literature Review (SLR) approach, this study analyzed 45 selected articles from international and national journals (2020–2025), which met inclusion criteria such as peer-reviewed status, relevance to Deming principles, TQM/PDCA, and sustainable education, as well as publication in indexed databases (Scopus, WoS, SINTA). The findings indicate that PDCA institutionalized through the PPEPP cycle in the Internal Quality Assurance System (SPMI) effectively enhances learning quality, participatory leadership, and reflective culture in both schools and universities. Cross-functional collaboration through PLCs/MGMPs, continuous innovation through kaizen, and future orientation through lifelong learning and digital literacy strengthen the implementation of  Education for Sustainable Development (ESD). Theoretically, this research integrates the Deming–ESD–CI paradigms into a single strategic model for sustainable education transformation; practically, it offers an operational roadmap for educational institutions and policymakers to develop quality systems that are collaborative, innovative, and adaptive to global change.